(untitled) (Journal of Applied Learning and Teaching, 2023)
This research engaged undergraduate students to design a learner-centric multi-disciplinary module that encompassed the three main pillars of sustainability, namely the economic, environmental, and social pillars of sustainability as well as the United Nations Sustainable Development Goals (SDGs). Collaborating in multi-disciplinary groups, participating students examined their learning experiences through the perspectives of educators while researching on sustainability and pedagogy. Both groups of students were provided with a framework of pedagogical approaches, such as flipped classroom, student-centred learning, collaborative learning, outcome-based learning, and formative assessment. Beyond the focus on sustainability as a subject matter and the pedagogical framework little guidance was provided during the creation process. Through their participation in the five-day bootcamp-style Module Design Workshop, both groups created an engaging and creative module that addressed their educational needs and expectations. Moreover, participating students clearly exhibited an increased understanding of pedagogy, sustainability, and the SDGs. Through pre-and post-workshop surveys and post-workshop group reports participating students illustrated a range of perceived and experienced challenges and takeaways, such as lack of time, lack of knowledge, changed perception of higher education pedagogy, and a sense of achievement. Observations throughout the Module Design Workshop found that both groups of students demonstrated their ability to work in multi-disciplinary teams and develop strategies to overcome difficulties. The research project has proven that both groups were able to create a well-designed module on sustainability, which could be offered to undergraduate students in order to facilitate sustainability education in all academic disciplines.